The Emerging Landscapes of Long Noncoding RNA in Thyroid Carcinoma: Biological Functions and Clinical Significance - Zhu, Jian; Liu, Changrui; Wang, Dan; Cao, Xianjiao; Wang, Shuai; Liu, Yixin; Wang, Jun; Li, Peifeng; He, Qingqing (Frontiers in Oncology, 2021)
Thyroid carcinoma (TC) is one of the most prevalent primary endocrine tumors, and its incidence is steadily and gradually increasing worldwide. Accumulating evidence have been demonstrated the essential functions of long noncoding RNAs (lncRNAs) in the initiation and development of TC. Many TC-associated lncRNAs have been documented to dysregulate and implicate in malignant phenotypes, including uncontrolled cell proliferation, gain of invasive capability and resistant to therapeutics, through interacting with proteins, DNA, or RNA or encoding small peptides. Therefore, deeply elucidating of lncRNA dysregulation shed additional insights into TC tumorigenesis and open new avenues for the early diagnosis and clinical therapy of TC. In this review, we summarize the abnormal expression of lncRNA in TC and the fundamental characteristics in TC tumorigenesis and development. Additionally, we introduce the potentially predictive and prognostic biomarkers and therapeutic significance of lncRNAs in TC.